Risks of shift workers in professional activity in Far North - Ya. A. Korneyeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Climatic, geographical, industrial and welfare factors make on the body of shift worker claims exceeding its reserves, which excludes the possibility of complete adaptation to these conditions and leads to the existence of occupational health hazards. In extreme conditions, shift work in the Far North would be assessed not only occupational risks, but also the risks to the health and psychological risks. Assessment of the risks to health workers suggests a wide range of criteria and indicators, which improves the timely development and implementation of preventive measures. Psychological assessment of risks in a professional activity would develop technology and conduct management activities, as moral hazard and risks to health.